New evidence of potential benefits of dexamethasone and added on therapy of fludrocortisone on clinical outcomes of corticosteroid in sepsis patients: A systematic review and meta-analysis - Son, Ji Young; Shin, Sooyoung; Choi, Yeo Jin (Journal of Personalized Medicine, 2021)
The aim of this study is to investigate clinical outcomes of corticosteroid treatment in patients with sepsis or septic shock. An electronic keyword searches of PubMed, EMBASE, and Google Scholar were conducted per PRISMA guidelines. The pooled analyses on the corticosteroid impact on mortality, adverse events, and clinical outcomes were performed. Subgroup analyses on the clinical outcomes in relation to corticosteroid dose, duration, and agents were performed. Pooled analyses of 21 randomized control trials revealed substantially reduced mortality (RR 0.93, 95% CI 0.88–0.99, p = 0.02) and length of stay in intensive care unit (SMD −1.66, 95% CI −1.91–−1.40, p < 0.00001) without increased risks of adverse events (RR 1.04, 95% CI 0.96–1.12, p = 0.38). No significant improvements of other clinical outcomes were observed. Subgroup analyses demonstrated substantially reduced mortality with short-term (≤7 days) low-dose (<400 mg/day) corticosteroid treatment (RR 0.91, 95% CI 0.87–0.95, p < 0.0001). Moreover, dexamethasone (RR 0.40, 95% CI 0.20–0.81, p = 0.01) and combined hydrocortisone and fludrocortisone treatment (RR 0.89, 95% CI 0.84–0.94, p < 0.00001) provided substantial reduction of mortality whereas hydrocortisone alone did not reduce the mortality risk in sepsis patients. Thus, further controlled studies on the clinical outcomes of potential corticosteroid options on sepsis-related clinical outcomes are warranted.
Keywords: Corticosteroid; Dexamethasone; Fludrocortisone; Mortality; Sepsis; Septic shock